The city and its uncertain walls eaudiobook A novel. - Murakami, Haruki (Books on Tape, 2024)
NEW YORK TIMES BESTSELLER • A GLOBE AND MAIL BEST BOOK OF THE YEAR • A REAL SIMPLE BEST BOOK OF THE YEAR • NEW YORK TIMES BESTSELLER From the author of Norwegian Wood and Hard-Boiled Wonderland and the End of the World comes a love story, a quest, an ode to books and to the libraries that house them, and a parable for our peculiar times. " Haruki Murakami invented 21st-century fiction." — The New York Times • " More than any author since Kafka, Murakami appreciates the genuine strangeness of our real world." —San Francisco Chronicle • " Murakami is masterful. " —Los Angeles Times We begin with a nameless young couple: a boy and a girl, teenagers in love. One day, she disappears . . . and her absence haunts him for the rest of his life. Thus begins a search for this lost love that takes the man into middle age and on a journey between the real world and an other world – a mysterious, perhaps imaginary, walled town where unicorns roam, where a Gatekeeper determines who can enter and who must remain behind, and where shadows become untethered from their selves. Listening to his own dreams and premonitions, the man leaves his life in Tokyo behind and ventures to a small mountain town, where he becomes the head librarian, only to learn the mysterious circumstances surrounding the gentleman who had the job before him. As the seasons pass and the man grows more uncertain about the porous boundaries between these two worlds, he meets a strange young boy who helps him to see what he’s been missing all along. The City and Its Uncertain Walls is a singular and towering achievement by one of modern literature’s most important writers. "Truth is not found in fixed stillness, but in ceaseless change/movement. Isn't this the quintessential core of what stories are all about?” —Haruki Murakami, from the afterword